2020
DOI: 10.1111/jppi.12338
|View full text |Cite
|
Sign up to set email alerts
|

Employees' experiences of education and knowledge in intellectual disability practice

Abstract: Background The value of support, service, and care in intellectual disability (ID) practice is linked to the competence of the professional caregivers. The quality of work is affected by the level of education of healthcare employees involved. Specific Aims This study aimed to collect data on how employees perceive their education and training in ID practice and how educational programs prepare them for their working environment. Methods We used a quantitative approach to investigate how employees reflect on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…As in the case of social care organizations, total employee involvement is considered a core dimension (Ghența et al, 2014) to meet the increasing demands of users. Various needs and objectives in the external environment require the total involvement of professionals (Olsson and Gustafsson, 2020) at both team and organizational levels. To reach Employees 'involvement, managers need to promote a new organizational culture and a proactive approach to employees.…”
Section: Tqmmentioning
confidence: 99%
“…As in the case of social care organizations, total employee involvement is considered a core dimension (Ghența et al, 2014) to meet the increasing demands of users. Various needs and objectives in the external environment require the total involvement of professionals (Olsson and Gustafsson, 2020) at both team and organizational levels. To reach Employees 'involvement, managers need to promote a new organizational culture and a proactive approach to employees.…”
Section: Tqmmentioning
confidence: 99%
“…These are environmental policy stringency, government financing, environmentally related innovation, and human capital. Proxies for environmental policy stringency were non-market-based policies [39,40] and market based policies [40,41], for government financing were gross domestic expenditure on R&D by source of funds [42], R&D expenditure intramural [43,44] and national expenditure on environmental protection [45,46], and environmentally related innovation and human capital proxies were patents to protect collaborative inventions of environmentally related technologies [47,48] and employees involved in education and training [49]. Table 2 below shows a detailed description of the variables, and their proxies used, as well as existing studies that used similar variables and data sources.…”
Section: Measurement Of Variablesmentioning
confidence: 99%
“…( 2019 ) and Umb Carlsson ( 2021 ) concluded that staffs’ working practices greatly affected the residents’ possibilities to achieve a healthy lifestyle. Studies have found that staff in housing feel that they do not have relevant knowledge to provide high quality support in that context (Olsson and Gustafsson 2020 , Hewitt and Larson 2007 ). While the real requirements are complex, the work is typically viewed as requiring little skills, and the staff turnover is traditionally high (Hewitt and Larson 2007 ).…”
Section: Introductionmentioning
confidence: 99%